RELATIONSHIP BETWEEN STUDENTS' READING HABIT AND THEIR READING COMPREHENSION - Alya Mahastra Putri; Asyfi hidayatu syabani; Davita Jasmine; Tria Moulina, (Journal of Applied Linguistics (ALTICS), 2024)
The goal of this study was to look at the association between students' reading habits and first-grade reading comprehension at SMA Jamiyatul Abror Al-GAZA. The authors employed questionnaires and tests to obtain data for this quantitative investigation with a correlational study. The questionnaire assesses students' reading habits, while the test assesses their reading comprehension. The population of this study included all first graders of Jamiyatul Abror Al-GAZA High School, with a sample size of 25 pupils drawn via purposive sampling. With a correlation coefficient of -0.017, the author concludes that there is no meaningful association between students' reading habits and their reading comprehension. This means that the alternative hypothesis (Hi) is rejected and the null hypothesis (Ho) is accepted, implying that in a modest correlation, there is no meaningful association between students' reading habits and their reading comprehension. To summarize, reading habits are not the only elements that influence students' reading comprehension; many other factors influence reading comprehension as well, including internal (intellectual, linguistic skills, psychological, contextual, and experience) and external (facilities, learning time). semantic abilities and cognitive comprehension are examples of ctic abilities. Keywords: Correlation, Reading Habit, Reading Comprehension.